قراءة في علم القافية بين التراث و المعاصرة - توفيق, عمر ابراهيم (Sulaimani Journal for Humanities, 2003)
This research is a rapid ,comprehensive and brief trip within the science of “rhyme” which laws were enacted by our ancestors and how they have been understand by the modernists , shedding light on the effect of the science of rhyme in the eastern world or the western rhyme in general, and the English rhyme in particular. The research studies the influence of the western innovative attempts to get rid of the mono-rhyme pattern of the Arabic literature through a comparative study of different rhyme potterns, as they have been clarified by western researchers and Arab innovators , depending on groups of somilar examples taken from both , the Arabic and English literature along various periods of time.